The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1094/mpmi-18-1325
|View full text |Cite
|
Sign up to set email alerts
|

The Coexistence of Symbiosis and Pathogenicity-Determining Genes in Rhizobium rhizogenes Strains Enables Them to Induce Nodules and Tumors or Hairy Roots in Plants

Abstract: Bacteria belonging to the family Rhizobiaceae may establish beneficial or harmful relationships with plants. The legume endosymbionts contain nod and nif genes responsible for nodule formation and nitrogen fixation, respectively, whereas the pathogenic strains carry vir genes responsible for the formation of tumors or hairy roots. The symbiotic and pathogenic strains currently belong to different species of the genus Rhizobium and, until now, no strains able to establish symbiosis with legumes and also to indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 51 publications
2
43
0
1
Order By: Relevance
“…Moreover, Velazquez et al (39) reported for the first time the occurrence of two strains (163C and ATCC 11325 T ) belonging to R. rhizogenes able to nodulate Phaseolus vulgaris. These strains displayed symbiotic plasmids carrying nod and nif genes phylogenetically related to those of E. meliloti.…”
mentioning
confidence: 99%
“…Moreover, Velazquez et al (39) reported for the first time the occurrence of two strains (163C and ATCC 11325 T ) belonging to R. rhizogenes able to nodulate Phaseolus vulgaris. These strains displayed symbiotic plasmids carrying nod and nif genes phylogenetically related to those of E. meliloti.…”
mentioning
confidence: 99%
“…The pathogenic strains of this legume endosymbiont contain vir genes, which cause the formation of tumors or hairy roots [76]. Strains of R. rhizogenes were shown to be able to induce hairy roots or tumors in plants and also to nodulate P. vulgaris under natural environmental conditions [76].…”
Section: Root-bacteria Interactionsmentioning
confidence: 99%
“…The pathogenic strains of this legume endosymbiont contain vir genes, which cause the formation of tumors or hairy roots [76]. Strains of R. rhizogenes were shown to be able to induce hairy roots or tumors in plants and also to nodulate P. vulgaris under natural environmental conditions [76]. In M. truncatula, a time-course analysis of root protein profiles was investigated using 2-DE and MS identification after inoculation with the nitrogen fixing bacterium Sinorhizobium meliloti.…”
Section: Root-bacteria Interactionsmentioning
confidence: 99%
“…However, no nif-like gene was discovered on the chromosome of A. tumefaciens strain C58 when the genome sequence of that bacterium was assembled. Nevertheless, recently, the coexistence of symbiosis and pathogenicity-determining genes has been shown to occur in strains of Rhizobium rhizogenes which enables them to induce nodules or tumours depending on plant species (Velá zquez et al 2005).…”
Section: Introductionmentioning
confidence: 99%